Pengembangan Bahan Ajar PAI pada Lembaga Pendidikan Vokasi dalam Era Digital - Mahdalena Juniarsih; Ahmad Hendrawan; Dina Handayani; Aa Nugraha; Arman Paramansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is to find out about Islamic Religious Education learning, specifically about PAI teaching materials at vocational institutions in the digital era. The method used is a qualitative methodology with data collected through the library research method. The data obtained in this method is based on facts, reality in the field and not designed by researchers through research research. The results of this research are that the first advantage of developing digital-based PAI teaching materials is wider affordability and accessibility. Through digital platforms, PAI teaching materials can be accessed by students anywhere and at any time, as long as they have internet access. The final challenge that must be overcome is the tendency to misuse technology.